2014
DOI: 10.1371/journal.pone.0111127
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Severe Fever with Thrombocytopenia Syndrome in Rural Regions of Zhejiang, China

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) infections have recently been found in rural regions of Zhejiang. A severe fever with thrombocytopenia syndrome (SFTS) surveillance and sero-epidemiological investigation was conducted in the districts with outbreaks. During the study period of 2011–2014, a total of 51 SFTSV infection cases were identified and the case fatality rate was 12% (6/51). Ninety two percent of the patients (47/51) were over 50 years of age, and 63% (32/51) of laboratory confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Similar to our findings, a previous study reported a low seroprevalence (2/237, 0.8%) of SFTSV antibodies in the general population of Yiyuan County, Shandong Province, China, in which more than 80% of the goats were positive for anti-SFTSV antibodies (16). In contrast, studies conducted in SFTS endemic regions in China have shown a higher seroprevalence (more than 5%) among healthy in- dividuals (17)(18)(19)(20). Furthermore, a recent study in South Korea reported that the seroprevalence of SFTS among patients visiting a tertiary hospital was 2.1%.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our findings, a previous study reported a low seroprevalence (2/237, 0.8%) of SFTSV antibodies in the general population of Yiyuan County, Shandong Province, China, in which more than 80% of the goats were positive for anti-SFTSV antibodies (16). In contrast, studies conducted in SFTS endemic regions in China have shown a higher seroprevalence (more than 5%) among healthy in- dividuals (17)(18)(19)(20). Furthermore, a recent study in South Korea reported that the seroprevalence of SFTS among patients visiting a tertiary hospital was 2.1%.…”
Section: Discussionsupporting
confidence: 89%
“…The SFTSV Seropositivity rate in China is 0.3%–9.2%, depending on the population group and region investigated (678910111213141516). However, no study has addressed the seroprevalence of SFTSV in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…However, some areas in China, with a similar environment as in endemic areas, SFTS cases have not been found. Furthermore, since 2010, when SFTSV was found to be the pathogen responsible for SFTS (3), serological surveys were conducted to understand SFTSV seroprevalence, which was found to be inconsistent (ranging from 0% to 9.2%) and rare, especially in non-endemic areas (14)(15)(16)20). Therefore, it is urgent to conduct investigations of SFTSV seroprevalence to know the infection status in such areas.…”
Section: Discussionmentioning
confidence: 99%